Physical Metallurgy of Light Alloys and Composite Materials - Belov, Nikolay A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The scope of this Special Issue focuses on the formation of the structure of light alloys, (particularly on an aluminum base) during solidification, deformation, and heat treatment and its relationship with mechanical and technological properties. The design of light alloys (including composite materials) based on experimental and theoretical studies is also considered. The Special Issue contains 11 papers, including 10 research papers and 1 review (on the asymmetric (hot, warm, cold, and cryo) rolling of light alloys).